2014 Joint Rail Conference 2014
DOI: 10.1115/jrc2014-3708
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Studies on Joint Bar Integrity: Part II — Finite Element Analyses

Abstract: This paper is the second in a two-part series describing research sponsored by the Federal Railroad Administration (FRA) to study the structural integrity of joint bars. In Part I, observations from field surveys of joint bar inspections conducted on revenue service track were presented [1]. In this paper, finite element analyses are described to examine the structural performance of rail joints under various loading and tie-ballast support conditions. The primary purpose of these analyses is to help interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…The magnitude of FEA IRJ deflections is in agreement with previous research. 26,27 All FE models showed that the deflection of an SUS-IRJ varies depending on the support stiffness. They proved that the additional deflection in an IRJ compared to that of a reference rail is lower when the model includes uniform support stiffness along the rail length, whereas this increases with the degradation of the track underneath the joint.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnitude of FEA IRJ deflections is in agreement with previous research. 26,27 All FE models showed that the deflection of an SUS-IRJ varies depending on the support stiffness. They proved that the additional deflection in an IRJ compared to that of a reference rail is lower when the model includes uniform support stiffness along the rail length, whereas this increases with the degradation of the track underneath the joint.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…for a suspended IRJ for various support conditions. 27 Finally, it was recently shown by a 2D vehicle-track model that the impact force P1 that mostly causes the track degradation due to the accordance of frequencies with those of the track is greatly influenced by the joint angle, the mass of the rail and the mass of the wheelsets, whereas the peak force P2 is mainly affected by the support stiffness at the joint angle apart from the mass of the wheelset and the railpad stiffness. 28 In the past, the track deflection for various wheel loads and track conditions has been measured.…”
Section: Modelling Of Irjsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, finite element analyses (FEA) are under development to help interpret the trends observed in field survey data. Moreover, FEA of bolted rail joints is the topic of the second paper in this two-part series [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Those discontinuities can cause high wheel impact loads, which might lead to rail end batter, loosened bolts, deteriorated support condition, and excessive deflection. Such defects can potentially lead to the following failure modes: bolt-hole cracks, head-web separation, bent or broken bolts, and cracked or broken joint bars [4,5]. Figure 1.…”
Section: Introductionmentioning
confidence: 99%